Statistical analysis for 134Cs and 137Cs radioactivity risk levels modeling - Bilici, Ahmet; Bilici, Sevim; Kulahci, Fatih (Springer, 2020)
After the Fukushima Dai-Ichi Nuclear Power Plant (FDNPP) accident,Cs-134 and Cs-137 were spread widely into the environment. Spatial distribution maps giving radiocesium activities in contaminated soils for post-accident risk modeling were obtained using the Kriging method. We used Generalized extreme-value distribution, Lognormal probability distribution (PDF) and Weibull PDFs for risk assessment of the data. Root mean square error values and coefficient of determination (R-2) were calculated for each distribution function. Weibull PDF was found to be more successful in modeling Cs-134 and Cs-137 activities. [GRAPHICS] .
Keywords: Risk analysis; Probability distribution function; Distribution functions; Modeling; Kriging